Spark plasma sintering and spark plasma upsetting of an Al-Zn-Mg-Cu alloy - TÜNÇAY, MEHMET MASUM (ELSEVIER SCIENCE SA, 2017)
Al-Zn-Mg-Cu alloy powder Alumix 431D was sintered at 400 degrees C by spark plasma sintering (SPS) and upset forging was applied to the sintered sample through SPS. Densities of 99.1 +/- 0.3% and 99.8 +/- 0.1% of theoretical were obtained for the sintered and forged samples, respectively. T6 temper was carried out on the samples and microstructure analysis and mechanical properties before and after heat treatment were evaluated. Microhardness of 173 +/- 3 and 172 +/- 3 HV were attained in the T6 temper of as-sintered and forged samples, respectively. The flexural strength and strain values were significantly improved after the forging process, which can be mainly attributed to the better particle bonding in addition to the occurrence of some recrystallization. Significant loss in the ductility was observed after the T6 temper.
Keywords: Spark plasma sintering; Forging; Al alloys; Mechanical properties; 7075 ALUMINUM-ALLOY; MECHANICAL-PROPERTIES; DYNAMIC RECRYSTALLIZATION; MICROSTRUCTURAL EVOLUTION; POWDER; CONSOLIDATION; BEHAVIOR; OXIDE; PRECIPITATION; PARTICLES